2001
DOI: 10.1073/pnas.021551098
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of soluble and wall-bound indolic metabolites in Arabidopsis thaliana leaves infected with virulent or avirulent Pseudomonas syringae pathovar tomato strains

Abstract: The chemical structures and accumulation kinetics of several major soluble as well as wall-bound, alkali-hydrolyzable compounds induced upon infection of Arabidopsis thaliana leaves with Pseudomonas syringae pathovar tomato were established. All identified accumulating products were structurally related to tryptophan. Most prominent among the soluble substances were tryptophan, ␤-D-glucopyranosyl indole-3-carboxylic acid, 6-hydroxyindole-3-carboxylic acid 6-O-␤-D-glucopyranoside, and the indolic phytoalexin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 39 publications
2
86
0
Order By: Relevance
“…Using soluble extracts from Arabidopsis thaliana leaves, we have previously shown that, in addition to the characteristic phytoalexin of this species, camalexin, several other indolic metabolites were strongly and rapidly induced upon infection. By contrast, the only major phenylpropanoid compound besides flavonoids, sinapoyl malate, decreased equally rapidly to very low levels, whereas all of the detectable flavonol glycosides remained largely unaffected (Hagemeier et al, 2001). Comparatively little is known about cell wall-bound substances in uninfected (Franke et al, 2002) and particularly in infected A. thaliana leaves, where so far only one indolic compound, indole-3-carboxylic acid, has been shown to accumulate in the cell wall upon compatible or incompatible interactions with a bacterial pathogen (Hagemeier et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Using soluble extracts from Arabidopsis thaliana leaves, we have previously shown that, in addition to the characteristic phytoalexin of this species, camalexin, several other indolic metabolites were strongly and rapidly induced upon infection. By contrast, the only major phenylpropanoid compound besides flavonoids, sinapoyl malate, decreased equally rapidly to very low levels, whereas all of the detectable flavonol glycosides remained largely unaffected (Hagemeier et al, 2001). Comparatively little is known about cell wall-bound substances in uninfected (Franke et al, 2002) and particularly in infected A. thaliana leaves, where so far only one indolic compound, indole-3-carboxylic acid, has been shown to accumulate in the cell wall upon compatible or incompatible interactions with a bacterial pathogen (Hagemeier et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…By contrast, the only major phenylpropanoid compound besides flavonoids, sinapoyl malate, decreased equally rapidly to very low levels, whereas all of the detectable flavonol glycosides remained largely unaffected (Hagemeier et al, 2001). Comparatively little is known about cell wall-bound substances in uninfected (Franke et al, 2002) and particularly in infected A. thaliana leaves, where so far only one indolic compound, indole-3-carboxylic acid, has been shown to accumulate in the cell wall upon compatible or incompatible interactions with a bacterial pathogen (Hagemeier et al, 2001). These findings raised two related questions: What else occurs in the cell wall upon infection, and what are the relative roles of phenylpropanoid and indolic metabolism in the two cellular compartments, particularly in view of the strong activation of biosynthetic genes for both classes of aromatic compounds in infected A. thaliana tissue (Ehlting et al, 1999;Zhao and Last, 1996).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular for tomato, results of Von Roepenack-Lahaye et al (2003) and those reported here, indicate that tomato plants challenged with P. syringae mainly accumulated HCAA of tyramine, dopamine, 575 octopamine and noradrenaline while, at least under our experimental conditions, no tryptophan-related or indolic substances were detected. Conversely, all the major accumulating soluble metabolites in leaves of Arabidopsis infected with P. syringae have been structurally identified as indolic tryptophan-related substances with the concomitant absence of phenylalanine derived metabolites (Hagemeier et al, 2001). 580…”
Section: (Trans-cna) (2) Trans-n-feruloylnoradrenaline (Trans-fna) (mentioning
confidence: 99%
“…Evidence has emerged during the past decades demonstrating the importance of products from the phenylpropanoid pathway in plant defence response against pathogens (Dixon et al, 2002;Jahangir et al, 2009). In recent years, very extensive and detailed studies on changes of metabolites in plant tissues have been carried out in 75 some plant pathogen interactions such as Arabidopsis/Pseudomonas syringae (Hagemeier et al, 2001;Tan et al, 2004), tobacco/tobacco mosaic virus (Choi et al, 2006) or saskatoons/Entomosporium mespili (Wolski et al, 2010). However, less is known regarding changes of the metabolic profile associated with the response of tomato plants to pathogens Zacarés et al, 2007).…”
mentioning
confidence: 99%